Multiscale Structural Health Monitoring of Cable-Anchorage System Using Piezoelectric PZT Sensors - Khac-Duy Nguyen; Jeong-Tae Kim; Young-Hwan Park (International Journal of Distributed Sensor Networks)
Structural health monitoring of the cable-anchorage system is very important to secure the integrity of the cable-stayed bridge. The cable-anchorage system carries most of the self-weight, so that any damage in the system may significantly reduce the load carrying capacity of the bridge. This study presents a multiscale structural health monitoring of the cable-anchorage system using piezoelectric PZT sensors. Firstly, the electromechanical impedance response is utilized for alerting the change in anchorage zone caused by the loss of cable force or local anchorage damage. Secondly, the dynamic strain of cable is utilized for classifying the damage type. Thirdly, the loss of cable force and the anchorage damage are quantified by a frequency-based cable force model and an impedance-based damage estimation model, respectively. The feasibility of the approach is evaluated from the experiment on a lab-scale cable-anchorage model for which several damage scenarios are simulated about cable damage and anchorage damage.